Murder, Sex, Corruption: Will China Continue to Hold Together? - Kjeld Erik Brødsgaard (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2012)
The recent Bo Xilai affair has created strains in the Chinese political system and has intensified the power struggle concerning the new leadership appointments due to take place at the 18th Party Congress. The pressure on the political system is intensified by a number of social phenomena such as increased fragmentation, vested interests, corruption, social unrest, increased income and social inequalities and a de facto reform stop since 2009. Some scholars believe that we now see the end of 'resilient authoritarianism' and that China either will experience a political and social collapse or move towards a democratic system. However, developments since 1989 show the regime's amazing ability to revitalize its organizational capabilities and regain its Mandate of Heaven. It may be too early to declare the Party over.
hdl:10398/8622
Keywords: 330; Corruption; Fragmentation; Vested interests; 'Resilient authoritarianism'; Future scenarios; Politische Instabilität; Soziale Stabilität; Korruption; Soziale Ungleichheit; China